Unity – Sexuality and Fertility: The Anthropology of Marriage and Family in the Teachings of Pope John Paul II and Pope Francis - Woźniak, Jakub J. (Studia Gdańskie, 2023)
This paper discusses the issue of the unity of man and woman in marriage from the standpoint of biblical anthropology. In its second chapter, it attempts to outline the significance of the difference between the sexes and sexuality, and in the third chapter, it addresses the problem of sin and portrays the distorted image of God in the human person and their relationship to both God and another person – in this case, the relationship of a husband to his wife and of a wife to her husband.